The degree of science teachers’ practice of methods of acquiring higher-order thinking skills in the intermediate stage in the State of Kuwait (Damascus University Journal of educational and Psychologyical sciences, 2025)
This study aimed to identify the degree to which science teachers in the intermediate stage in the State of Kuwait practice higher-order thinking skills (analysis, evaluation, and creativity) in their classrooms, as well as to identify the degree of differences in the degree to which science teachers practice these skills according to the variables of gender, academic qualification, and number of years of experience.  To answer the study questions and measure the results, the study used the descriptive analytical method and applied the study questionnaire after ensuring validity and reliability. The study sample consisted of 60 male and female teachers of science. It was found that there was a high degree among science teachers in practicing higher-order thinking skills related to the skills of analysis and innovation, and a very high degree in the evaluation skill. It also concluded that there are no statistically significant differences in the average scores of science teachers in the middle stage in the degree of their practice of higher-order thinking skills according to the gender variable, and that there are differences in the average degrees of science teachers in the middle stage’s use of higher-order thinking skills according to the academic qualification variable, in favor of educational teachers. Those with the highest arithmetic mean of 4.15, There were differences in the average degree of science teachers’ use of higher-order thinking skills in the intermediate stage according to the variable of years of experience. The differences were significant between the two groups (less than 5 years - from 5 to 10 years) in favor of teachers who had experience from (5 to 10 years) with the same average. The largest arithmetic mean was 4.26. The differences were also significant between the two groups (less than 5 years - more than 10 years) in favor of teachers with experience (more than 10 years) with the largest arithmetic mean. With a value of 4.28.
Keywords: : Higher thinking skills; Science subject; Science teachers